2016
DOI: 10.3389/fpsyg.2016.01808
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Correct Answer about The Dress’ Colors? Investigating the Relation between Optimism, Previous Experience, and Answerability

Abstract: The Dress photograph, first displayed on the internet in 2015, revealed stunning individual differences in color perception. The aim of this study was to investigate if lay-persons believed that the question about The Dress colors was answerable. Past research has found that optimism is related to judgments of how answerable knowledge questions with controversial answers are (Karlsson et al., 2016). Furthermore, familiarity with a question can create a feeling of knowing the answer (Reder and Ritter, 1992). Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The frequency of particular viewer types varies between studies (Chetverikov & Ivanchei, 2016;González Martín-Moro et al, 2018;Karlsson & Allwood, 2016;Wallisch, 2017). Using an unconstrained colour term choice methodology in the current study, we report an approximately even split between B&B and W&G viewers (similar to Aston & Hurlbert, 2017;Chetverikov & Ivanchei, 2016;Hesslinger & Carbon, 2016;Karlsson & Allwood, 2016;Schlaffke et al, 2015;Vemuri et al, 2016;Winkler et al, 2015). We further confirm that several individuals reported seeing the ambiguous Dress picture as B&Br (Aston & Hurlbert, 2017;Lafer-Sousa et al, 2015;Mahroo et al, 2017;Wallisch, 2017;Witzel et al, 2017).…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The frequency of particular viewer types varies between studies (Chetverikov & Ivanchei, 2016;González Martín-Moro et al, 2018;Karlsson & Allwood, 2016;Wallisch, 2017). Using an unconstrained colour term choice methodology in the current study, we report an approximately even split between B&B and W&G viewers (similar to Aston & Hurlbert, 2017;Chetverikov & Ivanchei, 2016;Hesslinger & Carbon, 2016;Karlsson & Allwood, 2016;Schlaffke et al, 2015;Vemuri et al, 2016;Winkler et al, 2015). We further confirm that several individuals reported seeing the ambiguous Dress picture as B&Br (Aston & Hurlbert, 2017;Lafer-Sousa et al, 2015;Mahroo et al, 2017;Wallisch, 2017;Witzel et al, 2017).…”
supporting
confidence: 80%
“…Results from the classroom study yielded three self-reported viewer types: the expected B&B and W&G viewers, but also the previously mentioned group of B&Br viewers. The frequency of particular viewer types varies between studies (Chetverikov & Ivanchei, 2016;González Martín-Moro et al, 2018;Karlsson & Allwood, 2016;Wallisch, 2017). Using an unconstrained colour term choice methodology in the current study, we report an approximately even split between B&B and W&G viewers (similar to Aston & Hurlbert, 2017;Chetverikov & Ivanchei, 2016;Hesslinger & Carbon, 2016;Karlsson & Allwood, 2016;Schlaffke et al, 2015;Vemuri et al, 2016;Winkler et al, 2015).…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…The observation that prior experience with disambiguating images influences the perception of the dress indicates the important role of top-down influences on the perception of the dress ( Witzel, Racey, et al, 2016 ; Witzel et al, 2017 ). Further support for this idea comes from an fMRI study according to which white-gold seers have a stronger activation of brain regions critically involved in high-level processing, such as frontal and parietal brain areas ( Schlaffke et al, 2015 ), from a study that found delayed visually evoked potentials in white-gold seers, which are indicative for the activation of higher cortical brain areas ( Rabin et al, 2016 ), and from evidence for the role of beliefs about the real scene in the perception of the dress ( Karlsson & Allwood, 2016 ).…”
Section: Introductionmentioning
confidence: 99%